Stigma, Religion, and Collective Identity: The Transformation of Former Thugs in Solo - Warsito, Warsito; Suratno, Suratno; Nainin, Dasrizal Marah (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study argues that the former thugs make an effort to rehabilitate their spoiled identity into a new identity collectively by presenting themselves on the front stage with a religious background. The former thugs change their appearance, spiritual behavior, ideological views, and economic management to create a new impression. This study employs a qualitative research approach with a phenomenological perspective. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis techniques consist of three stages: data reduction, data presentation, and conclusion. This study asks what the former thugs behave in the front stage? How do they navigate their identity to remove the stigma? This study finds that to navigate their identity, former thugs join the Islamic group, they change their nickname to a good nickname that shows their Islamic identity, they use their wealth to support religious activities and use it for something that is in accordance with Islamic teachings. They make these changes with their friends in the Islamic group collectively. This study incorporates Erving Goffman's theory, which posits that people in the West who have spoiled identities navigate their identities individually. In contrast, former thugs in Solo navigate their collective identity.